POLICY NETWORK IN THE IMPLEMENTATION OF SCHOOL-BASED QUALITY IMPROVEMENT MANAGEMENT POLICIES IN STATE BASIC SCHOOL OF KOTA BANDUNG - Ine Mariane (Lembaga Penelitian Universitas Pasundan, 2019)
This study at the Bandung City Primary School. The problems faced by the effectiveness of the Policy Network based on implementing organizations, policy objectives, policies, and policy environment in the Implementation of School-Based Quality Improvement Management Policies (MPMBS) in Bandung City Primary Schools (SDN). The concept used in this study is about the Smith's policy network.Interaction among actors in the network that will determine how policies should be implemented as the core of the network govern that focuses on interorganizational networks. This policy is used to analyze policies; implementing organizations, policy objectives, policies and policy environment. This study uses a qualitative approach with case study methods, it is based on the focus of research studies that require researchers to explore various aspects of MPMBS in Bandung based on the perceptions and experiences of informants through in-depth interviews, observation participants, and data triangulation. The informants in this study were the Head of the Education Office, the Head of the Curriculum Section of the Education Office, the Education Council and the School Supervisor, the SDN Principal, Teachers in the Curriculum and Student Affairs, School Committees, and Companies in the City of Bandung. The results showed that the policy network in the implementation of the MPMBS policy in Bandung City Elementary School has not been effective, because of the implementation of organizational factors in this case the Bandung City Education Office has not fully carried out its duties, responsibilities and responsibilities in the implementation of the MPMBS policy. As a policy target, the principal has not acted as an innovative and creative leader, the school board has not fully directed, provided input, and monitored the implementation, the school committee also has not acted as an advisor, supporter, controller and mediator for schools. Likewise from environmental factors, Public Elementary Schools in Bandung City have been able to explore the potential, aspirations and community participation of the business world. Research findings, policy networks in the implementation of MPMBS policy must be synergized between government, society and the private sector by building trust, commitment, rules, innovative leadership by managing existing resources and paying attention to the value of the system that applies to the public interest and equal opportunities.